Development of a problem-solving ability learning model for children with intellectual disabilities - Thiyaporn Kantathanawat; Asamaporn Treearpornwong; Mai Charoentham (Journal of Education and Health Promotion)
BACKGROUND: Enhancing problem-solving abilities (PSA) in children with intellectual disabilities is critical for fostering independence and adaptive skills. The initial PCTL- model integrated phenomenon-based learning (PhBL), cognitive coaching (CC), task analysis (TA), and optimal learning environments (LE) to address the unique educational needs of this population. MATERIAL AND METHODS: The study employed a two-phase approach. In phase 1, a conceptual framework for the PCTL model was synthesized through a systematic review of existing literature and an analysis of the teaching contexts specific to children with intellectual disabilities. In phase 2, the model was evaluated by eight educational experts specializing in curriculum design, assessment, special education, and technology. Quantitative ratings were collected to assess feasibility, utility, propriety, and accuracy, with an overall mean of 4.40 (SD = 0.51), indicating high appropriateness. Qualitative feedback was analyzed to refine the model, which was subsequently expanded and became the PCTL + PSA model. RESULTS: The expert panel validated the PCTL model, emphasizing its comprehensive structure and practical applicability. The model after expert assessment and input was expanded to five key components for developing PSA. Moreover, PSA is identified as being involved in identifying problems, subdividing problems, analyzing and proposing solutions, evaluating methods, and assessing outcomes. Across all evaluation dimensions, the PCTL + PSA model achieved high scores, with the utility dimension rated the highest (mean = 4.69, SD = 0.49, P < 0.05). The findings highlighted the importance of fostering a supportive LE—physically, psychologically, socially, and informationally—to maximize the model’s effectiveness. CONCLUSION: This study introduces a validated and practical framework tailored to enhance problem-solving skills in children with intellectual disabilities. The final PCTL + PSA model contributes to inclusive education by addressing the unique learning needs of this population and providing actionable strategies for educators to improve classroom practices.